Takotsubo cardiomyopathy associated with serotonin syndrome in a patient with stroke: A case report. Issue 13 (March 2019) - Jang, Sung Ho; Nam, Jong-Ho; Lee, Jun; Chang, Min Cheol
Abstract: Rationale: Takotsubo cardiomyopathy (TC) is characterized by transient left ventricular dysfunction. We describe a patient with stroke who presented with TC caused by serotonin syndrome (SS) following the administration of serotonergic and dopaminergic agents. Patient concerns: A 55-year-old man with stroke was administered venlafaxine, tianeptine, ropinirole, carbidopa/levodopa, bromocriptine, and methylphenidate during rehabilitation. The patient presented with clinical features of SS (mental confusion, agitation, hyperhidrosis, chills, rigidity, and tachycardia), which persisted over 24 hours. The day after his SS symptoms disappeared, the patient's blood pressure decreased, and he developed tachycardia. Diagnoses: Echocardiography revealed an extensively akinetic apical segment and a severely hypokinetic midventricular segment of the left ventricle with basal hyperkinesia. The ejection fraction was reduced to 38%, and he was diagnosed with TC by the cardiologist. Interventions: He was administered oxygen at 8 to 10 L/minutes via a Venturi mask, and norepinephrine bitartrate was administered intravenously. Hydration was maintained with normal saline infusion. Outcomes: Following appropriate management of TC, the patient was hemodynamically stable with significant recovery of his left ventricular wall motion. Lessons: Prognosis of TC is usually favorable; however, it could be fatal in some cases. Clinicians should be aware of the potential development of TC in patients with stroke presenting with SS following the administration of serotonergic and dopaminergic agents.